The Iddah Period in the Perspective of Women's Sexual and Reproductive Health - Indrayani, Diyan; Ferina, Ferina; Trisiani, Desi; H. Abdul-Mumin, Khadizah (Perhimpunan Intelektual Muslim Indonesia, 2024)
Divorce cases in Indonesia in 2022 will increase to 15.31% compared to the previous year. QS research. Al Baqarah: 228 regarding the discussion of iddah time. Iddah is a period determined by syara' for a woman after a divorce to refrain from marrying another man and this is considered to discriminate against women. This is a narrative review. data source taken from PubMed Database and Google Scholar. The period of Iddah and Reproductive Health was searched systematically with the inclusion criteria of full text articles published within the last 5 years. A search using a combination of key terms, including 'divorce', 'iddah period', 'sexual health', reproductive health', Immune system, resulted in a final data set that included 7 studies. The Iddah period is related to making sure to know the possibility of getting pregnant or not and to know the cleanliness of the uterus. This aims to preserve offspring and prevent mixing of offspring from previous men or husbands. The cleaning period for the reproductive organs takes 120 days. Women's immunity has a genetic memory of sperm for 120 days. In addition, this period can also prevent sexually transmitted diseases due to decreased immunity which can occur due to the influence of free relationships and multiple partners. The Iddah period has an impact on cleaning the female reproductive organs, straightening lineages to avoid mixing lineages, and preventing sexually transmitted diseases and is not a discrimination. This needs to be understood from the scientific aspect of health and Islamic law as educational material for the community